Hepatic micro‐abscesses as an unusual initial presentation of systemic lupus erythematosus: A case report - Sreethish Sasi (14151873) (2024)
Key Clinical Message Hepatic micro‐abscesses can be a rare initial presentation of systemic lupus erythematosus (SLE). This case highlights the importance of considering autoimmune etiologies when infectious causes are ruled out and emphasizes the need for early recognition and appropriate treatment of atypical hepatic manifestations in SLE to achieve favorable outcomes. Systemic lupus erythematosus (SLE) is an autoimmune disease that affects multiple organs, including the liver. While hepatic involvement in SLE is typically subclinical or associated with mild liver enzyme elevations, rare manifestations such as hepatic micro‐abscesses and hepatic vasculitis have been reported. We report the case of a 27‐year‐old female who presented with persistent high‐grade fever, bilateral exudative lymphocytic pleural effusion, hepatic micro‐abscesses, anemia, and lymphopenia. Despite extensive investigations and antibiotic therapy, the patient's condition continued to worsen. The diagnosis of hepatic vasculitis, a rare manifestation of SLE, was ultimately made based on clinical suspicion, positive autoimmune markers, and negative septic workup. The patient responded well to high‐dose corticosteroid therapy and intravenous immunoglobulin, with resolution of liver lesions and clinical improvement. Hepatic involvement in SLE is diverse, and atypical presentations can pose diagnostic challenges. Hepatic vasculitis, although rare, should be considered in SLE patients presenting with liver lesions. The management involves immunosuppressive therapy, and prompt diagnosis is crucial to prevent further vascular damage. Hepatic micro‐abscesses, another rare manifestation of SLE, are thought to result from immune complex deposition. The exact pathogenesis remains unclear. Hepatic micro‐abscesses can have both infectious and non‐infectious causes, and it is very important to rule out common microbial pathogens. Treatment focuses on managing the underlying SLE activity with immunosuppressive agents. This case highlights the diagnostic challenges and management considerations in atypical hepatic manifestations of SLE. Awareness of rare presentations and collaboration among multiple specialties are essential for accurate diagnosis and appropriate treatment. Other Information Published in: Clinical Case Reports License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1002/ccr3.8586